2016
DOI: 10.17235/reed.2016.4441/2016
|View full text |Cite
|
Sign up to set email alerts
|

Practical aspects of high resolution esophageal manometry

Abstract: High resolution esophageal manometry (HRM) is currently under development as can be seen in the various Chicago classifications. In order to standardize criteria in certain practical aspects with limited scientific evidence, the First National Meeting for Consensus in High Resolution Manometry of the Spanish Digestive Motility Group took place, bringing together a wide group of experts. The proposals were based on a prior survey composed of 47 questions, an exhaustive review of the available literature and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 78 publications
0
3
0
1
Order By: Relevance
“…The normal ranges were as follows, LES length: 2.7-4.8 cm, LES basal pressure: 13-43 mmHg, IRP: < 15 mmHg, UES basal pres-sure: 34-104 mmHg, UES relaxation pressure: < 12 mmHg, DCI: 500-5000 mmHg • cm • sec (hypercontractile if DCI > 8000 mmHg • cm • sec and ineffective if DCI < 450 mmHg • sec • cm), CFV: < 9 cm/s, premature contraction was considered if DL was < 4.5 seconds, small peristaltic breaks was defined as 2-5 cm defects in the 20 mmHg isobaric contour and large peristaltic breaks was defined as defects > 5 cm in the 20 mmHg isobaric contour. Hiatal hernia was defined as a separation between the LES and crural diaphragm of > 2 cm (10).…”
Section: Esophageal High Resolution Manometrymentioning
confidence: 99%
See 1 more Smart Citation
“…The normal ranges were as follows, LES length: 2.7-4.8 cm, LES basal pressure: 13-43 mmHg, IRP: < 15 mmHg, UES basal pres-sure: 34-104 mmHg, UES relaxation pressure: < 12 mmHg, DCI: 500-5000 mmHg • cm • sec (hypercontractile if DCI > 8000 mmHg • cm • sec and ineffective if DCI < 450 mmHg • sec • cm), CFV: < 9 cm/s, premature contraction was considered if DL was < 4.5 seconds, small peristaltic breaks was defined as 2-5 cm defects in the 20 mmHg isobaric contour and large peristaltic breaks was defined as defects > 5 cm in the 20 mmHg isobaric contour. Hiatal hernia was defined as a separation between the LES and crural diaphragm of > 2 cm (10).…”
Section: Esophageal High Resolution Manometrymentioning
confidence: 99%
“…Previous studies have shown a higher frequency of esophageal dysmotility in GERD with globus rather than GERD with typical symptoms (7)(8)(9). High-resolution manometry (HRM) is a useful tool in evaluating esophageal motility (10) and this study aimed to compare the esophageal motility between GERD patients with and without globus symptoms. We speculated that different esophageal motility may contribute to the different symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Desde que la MAR esofágica se introdujo en la práctica clínica, se han desarrollado cambios técnicos y metodoló-gicos, por esto se requiere una estandarización, establecimiento de valores de referencia y criterios de análisis entre los laboratorios (12). Realizar un estudio de MAR de alta calidad requiere controlar ciertos aspectos relacionados con el paciente y la ejecución técnica del procedimiento, como se describe a continuación.…”
Section: Cómo Realizar Un Estudio De Alta Calidadunclassified
“…The development of esophageal high-resolution manometry (HRM) has resulted in significant improvements in the identification and classification of esophageal motor disorders (1,2). Digital data acquisition with HRM has allowed the development of intuitive software tools that address resistance to flow across the esophagogastric junction (EGJ) during swallows (integrated relaxation pressure, IRP), the vigor (distal contractile integral, DCI) and timing of smooth muscle contraction (distal latency, DL) (3).…”
Section: Introductionmentioning
confidence: 99%